KEPENTINGAN KANADA MELAKUKAN HUBUNGAN PERDAGANGAN BEBAS DENGAN KOREA SELATAN - Silvia Ardina Putri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research that the study of the international of economic political analyzes about the interest of canada to do trading free trade relationship with south korea. The purpose of this reasearch is to describe in general of the bilateral relations of canada and south korea in trading activities, explaining of the canada interests to do free trade agreement with south korea and also describe of cooperation does canada and south korea in the frame of the CKFTA's Agreement.This research used qualitative methods which is done by explanning the case based on existing facts. The techniques used to collects data to study the case to library research in the form of journals, books, an official document, articles, and websites. The theoretical framework applied in this research are liberalism perspective, international cooperation theory, and nation-state analysis. the international cooperation is a form of relations made by a country with another country, which has the purpose to sufficent the needs of life and the existence of a country in international social order, in addition to the creation of peace and prosperity of life that be desire of every human being and country in the world.The bilateral relations of Canada and South Korea have been well established for a long time, both in the political, economic and cultural fields. In addition, Canada and South Korea are both developed countries, located in different continents. Then, to further strengthen the relationship, these two countries to enter into free trade agreements contained within the framework of the CKFTA agreement. This CKFTA agreement framework represents the interests of both countries of economic, political and cultural. It's same with Canada who expects to benefit from the implementation of CKFTA agreement by through a reduction to eliminate tariffs policy and increase market access within the Asia Pacific region.Keyword: Interest, Free Trade Relations, CKFTA, International CooperationTheory, Liberalism, Political Economy Interest.